Pengaruh brand ambassador, brand association dan brand loyalti terhadap keputusan pembelian Neo Coffee - Subiyakto, Gatot; Nadiani, Zalfa Putri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of Brand Ambassador, Brand Association, Brand Loyalty on Neo Coffee Purchase Decisions. The analytical method in this study uses quantitative primary data. The test stages carried out are validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, t test (partial), f test (simultaneous), and coefficient of determination analysis (R2). The data used in this study used a questionnaire instrument, and the valid data collected were 100 respondents. The testing tool used is SPSS 24. The results showed that partially (individually) the brand association variable did not have a positive and significant effect on consumer purchasing decisions. Then the brand ambassador and brand loyalty variables have a positive and significant influence on consumer purchasing decisions. And simultaneously (overall) the variables of brand ambassador, brand association and brand loyalty have a positive and significant effect on consumer purchasing decisions in Jabodetabek.